Employees’ Whistle-Blowing Intention In The Banking Industry - Cheng, Chee Wei (2021)
In Malaysia, due to increasing corporate scandals involving fraudulent acts and organization mismanagement, Malaysian Government has enacted the Whistleblower Protection Act 2010 (WPA 2010) which took effect on 15 December 2010. All organizations are required to comply with the WPA 2010. As guided by Bank Negara, the bank is responsible to provide whistleblower protection and is obliged to create a working culture which encourages employees to report any wrongdoing without fear of retaliation. All banks have implemented their whistle-blowing policy as an action plan to adhere WPA 2010. Despite the multiple studies performed on the topic of whistle-blowing, there is no empirical study in Malaysia to examine whistle-blowing intentions among employees working in financial institutions. The objective of this study is to examine the employees’ whistle-blowing intentions in the banking industry. This study adopts the Theory of Planned Behavior and Perceived Organizational Support Theory as underlying models to examine the relationship between attitude, perceived organizational support, personal cost of reporting and ethical responsibility for reporting. The data was analyzed using Statistical Package for Social Sciences software (SPSS) and Structural Equation Modeling (SEM). Based on the analysis result, it demonstrated that internal and external whistle-blowing are significantly influenced by perceived organizational support and ethical responsibility for reporting. Meanwhile, attitude is influencing the employees’ internal whistle-blowing intention while personal cost of reporting is influencing the employees’ external whistle-blowing intention. There is negative relationship between attitude and external whistle-blowing intention. The relationship between personal cost of reporting and internal whistle-blowing intention is also insignificant. The finding is consistent with previous researchers.